Exploring soil organic carbon fractions, stocks, and carbon management index across land uses in subtropical ecosystems of Tripura, India - Meena, Siyaram; Manjaiah, K. M.; Sharma, V. K.; Purakayastha, T. J.; Das, Shrila; Bana, Ram Swaroop; Gawdiya, Sandeep; Yadav, Sunita; Saini, Ravi; Kumar, Anil; El-Hendawy, Salah; Mattar, Mohamed A.; et al. (Frontiers in Sustainable Food Systems, 2025)
Soil organic carbon (SOC) is vital for ecosystem health, improving soil quality, enhancing productivity, and acting as a significant carbon sink for climate change mitigation. Understanding the distribution of SOC across various land uses is essential for developing effective land management strategies that enhance soil health and carbon sequestration. This study aimed to evaluate the sensitivity of SOC fractions, including readily oxidizable carbon, total organic carbon (TOC), carbon stocks, and carbon management index (CMI), across different land use systems (LUSs) in Tripura, India. Soil samples were collected from horticultural and agricultural LUSs (oil palm, litchi, citrus, guava, rubber, ginger, rice–fallow, vegetable cowpea–rice–maize, vegetable cowpea–rice–lentil, vegetable cowpea–rice–mustard, and uncultivated), at five soil depths: 0–15, 15–30, 30–60, 60–75, and 75–100 cm. The samples were analyzed for various physical and chemical properties, SOC fractions, carbon stock, and CMI to assess the role of LUSs in managing soil carbon content. Significant differences were observed in SOC fractions, carbon stock, and CMI across the LUSs. Litchi LUSs exhibited the highest organic carbon content (16.6 g kg−1) and TOC (22.2 g kg−1) at 0–15 cm, while uncultivated land recorded the lowest values. SOC fractions showed a significant decrease with increasing soil depth from 0 to 100 cm. Litchi orchards had the highest average SOC stock (41.2 Mg ha−1) and readily oxidizable carbon (1.72 g kg−1), followed by rubber and oil palm. Rubber showed the highest lability index, followed by litchi and oil palm with values of 1.47, 1.41 and 1.39, respectively. Litchi and rubber exhibited the highest carbon pool index values, indicating substantial carbon retention. Furthermore, litchi, rubber, and oil palm exhibited significantly higher CMI values, with 245, 238, and 222, respectively. The study emphasizes the significant role of different LUSs, particularly horticultural land use, in enhancing SOC fractions and carbon sequestration. The findings suggest that integrating such LUSs, like litchi and rubber, can contribute significantly to improving soil quality and implementing effective climate change mitigation strategies.